x^{2} - 2x - 4y + 9 = 0 continued:

B. (x - 2)^{2} = 4(y - 3); vertex: (1, 2); focus: (1, 3) ; directrix: y = 3

C. (x - 1)^{2} = 4(y - 2); vertex: (1, 2); focus: (1, 3) ; directrix: y = 1

D. (x - 1)^{2} = 2(y - 2); vertex: (1, 3); focus: (1, 2) ; directrix: y = 5

Thank you for the opportunity to help you with your question!

the answer should be (x-1)^2=4(y-2); vertex: (1,2); focus: (1,3); directrix: y=1

so the answer is B!

best me please, I guarantee the answer is 100% correct thank you

Secure Information

Content will be erased after question is completed.

Enter the email address associated with your account, and we will email you a link to reset your password.

Forgot your password?

Sign Up